Analisis mediasi moderasi pada interaksi persepsi beban kerja rendah dan kebosanan kerja - Parahyanti, Endang; Rihhandini, Don Ozzy; Zharifah, Afiyah Tsarwat (Persona:Jurnal Psikologi Indonesia, 2022)
Abstract Millennial employees experience twice as much boredom at work as the previous generation. They often feel bored because lack of challenges and meaning in work and perceive their work as underloading. This study aimed to examine the mediating role of positive meaning in work in the relationship between the perception of underload work and boredom at work and to see whether that mediation relationship depends on increasing challenging job demands. The instruments used are boredom at work scale (∝ = 0.714), perception of underload work (∝ = 0.75), positive meaning in work (∝ = 0.87), and increasing challenging job demands (∝ = 0.83). The sampling technique used was purposive sampling with the characteristic employee born from 1982 to 1999 who had already worked at their current job for a minimum of six months. Data analysis used PROCESS HAYES model 4 for the mediation model and model 14 for the moderation mediation model. Data obtained from 327 participants showed that positive meaning in work mediated the relationship between the perception of underload work and boredom at work, and increasing challenging job demands had also been found as a moderating role in the relationship between positive meaning in work and boredom at work. Keywords: boredom at work; increasing challenging job demands; perception of underload work; positive meaning in work; millennials. Abstrak Karyawan milenial mengalami kebosanan kerja dua kali lebih sering dibandingkan generasi-generasi sebelumnya. Karyawan milenial sering merasa bosan karena kurangnya tantangan dan makna di dalam pekerjaannya, serta mempersepsikan pekerjaan mereka memiliki beban kerja yang rendah. Penelitian ini bertujuan untuk melihat peran mediasi positive meaning in work dalam hubungan antara persepsi beban kerja rendah dan kebosanan kerja, serta untuk melihat hubungan mediasi tersebut apakah tergantung dari increasing challenging job demands. Instrumen yang digunakan adalah skala kebosanan kerja (∝ = 0.714), persepsi beban kerja rendah (∝ = 0.75), positive meaning in work (∝ = 0.87), dan increasing challenging job demands (∝ = 0.83). Teknik sampling yang digunakan adalah purposive sampling dengan kriteria karyawan yang lahir pada tahun 1982-1999 dan telah bekerja minimal 6 bulan pada pekerjaan saat ini. Analisis data menggunakan PROCESS HAYES model 4 untuk model mediasi dan model 14 untuk model mediasi moderasi. Data dari 327 partisipan menunjukkan bahwa positive meaning in work memediasi hubungan antara persepsi beban kerja rendah dan kebosanan kerja dan increasing challenging job demands juga ditemukan memiliki peran moderasi dalam hubungan positive meaning in work dan kebosanan kerja. Kata Kunci: kebosanan di tempat kerja; increasing challenging job demands; persepsi beban kerja rendah; positive meaning in work; millennial.